Chlorine Decay Modelling to Predict Disinfectant and Disinfectant by-Products (DBPs) Formation in Water Distribution System - Jabari Kohpaei, Ahmad (Curtin University, 2018)
The objective of this research project is to understand chlorine decay and formation of disinfectant by-products (DBPs) using existing popular chlorine decay models. Performance of various chlorine decay models for different waters was investigated. Defining main performance criteria, popular models were modified to produce more reliable predictions. Nominated chlorine decay models were compared against defined criteria. Best chlorine decay model was endorsed. Finally, chlorine decay and formation of DBPs in a water distribution system was modelled as a case study.